2021
DOI: 10.3390/ijerph18094802
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Conditioning of the Development of the COVID-19 Pandemic and Its Global Spatial Differentiation

Abstract: The COVID pandemic very quickly became the world’s most serious social and economic problem. This paper’s focus is on the spatial aspect of its spread, with the aims being to point to spatial conditioning underpinning development of the pandemic, and to identify and assess possible socio-economic features exerting an impact on that. Particular attention has been paid to the percentage of positive tests for the presence of the coronavirus, as well as mortality due to the disease it causes. The statistics used r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…While about one half of the studies point towards the positive link ( Gonzalez-Val & Sanz-Gracia, 2021 ; Kianfar, Mesgari, Mollalo, & Kaveh, 2022 ; Li, et al, 2021 ), the other half of them had shown no association ( Kumru, Yiğit, & Hayran, 2021 ; Teh, et al, 2021 ). Only a handful of studies have examined the role of measures of income level ( Leung, Sharma, Adithipyangkul, & Hosie, 2020 ; Li, et al, 2021 ), amount of education ( Li, et al, 2021 ; Bański, Mazur, & Kamińska, 2021 ), unemployment ( Jain & Singh, 2020 ) or household size ( El Mouhayyar, Jaber, Bergmann, Tighiouart, & Jaber, 2021 ) on infection rate. Perhaps this is because of two reasons.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…While about one half of the studies point towards the positive link ( Gonzalez-Val & Sanz-Gracia, 2021 ; Kianfar, Mesgari, Mollalo, & Kaveh, 2022 ; Li, et al, 2021 ), the other half of them had shown no association ( Kumru, Yiğit, & Hayran, 2021 ; Teh, et al, 2021 ). Only a handful of studies have examined the role of measures of income level ( Leung, Sharma, Adithipyangkul, & Hosie, 2020 ; Li, et al, 2021 ), amount of education ( Li, et al, 2021 ; Bański, Mazur, & Kamińska, 2021 ), unemployment ( Jain & Singh, 2020 ) or household size ( El Mouhayyar, Jaber, Bergmann, Tighiouart, & Jaber, 2021 ) on infection rate. Perhaps this is because of two reasons.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition, Peru became the country with the highest COVID-19 case fatality rate in the world, despite the efforts made by the government, evidencing the collapse of its health system. 14 16 From all the above, it can be understood that the residents of Peru had to survive a complex and challenging context, which not only put their lives and those of their families at risk, but also compromised the economic stability of their homes; therefore, the performance of practices that did not need to be addressed urgently, such as dental brushing for children, was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that major spatial aspects underpin differentiated impacts of the pandemic. Besides geography influencing the spread and magnitude of the effect of coronavirus, Bański et al (2021) posit that socioeconomic conditioning determines the severity of impacts of the pandemic. Furthermore, as earlier stated by Snow et al (2021) , a high level of ingenuity among local communities precipitated the resilience of New Zealand and the Australian agriculture sector to coronavirus disruptions.…”
Section: Case Descriptionmentioning
confidence: 99%